The Role of Social Support and Self-Efficacy on Resilience of Late Adolescence with Divorced Parents - Afifah, Jihan Nur; Trimulyaningsih, Nita (Universitas Islam Indonesia, 2025)
Resilience is a crucial ability for late adolescents with divorced parents to face daily life post parental issues. In this context, social support and self-efficacy have a relationship and role with resilience. Therefore, this research aimed to show the simultaneous relationship between social support and self efficacy with resilience using a quantitative method. Data collection tools used were The Connor-Davidson Resilience Scale (CD-RISC), The Multidimensional Scale of Perceived Social Support (MSPSS), and the General Self Efficacy Scale (GSES). The subjects were 105 late adolescents with divorced parents in Indonesia. Furthermore, Pearson correlation analysis and multiple linear regression were adopted. The results showed that social support and self-efficacy had a significant positive influence on resilience. The higher the role of social support and self-efficacy, the greater resilience of late adolescents with divorced parents. The results had implications for managing social support with self-efficacy to increase resilience in late adolescents with divorced parents.